Using qualitative risk assessment to re-evaluate the veterinary fence paradigm within the Kavango Zambezi Transfrontier Conservation Area - Rosen, Laura E.; Atkinson, Shirley J.; Babayani, Nlingisisi D.; Mokopasetso, Mokganedi; Penrith, Mary-Louise; Ramsden, Nidhi; Sharpe, Janine; Shuro, Thompson; Thololwane, Odireleng I.; van Rooyen, Jacques; Osofsky, Steven A. (Frontiers in Veterinary Science, 2026)
IntroductionHabitat connectivity in southern Africa’s Kavango Zambezi Transfrontier Conservation Area (KAZA TFCA, or KAZA) is hindered by the presence of veterinary fences put in place to prevent transboundary animal disease transmission. In northern Botswana’s Ngamiland, much of the fencing infrastructure is in disrepair due to ineffective maintenance in the face of increased elephant damage, but specific sections of some fences still restrict critical wildlife movements.MethodsWe undertook qualitative risk assessments for sections of the Northern Buffalo fence near the Okavango Delta and the Zambezi Border and Western Border fences along the Botswana-Namibia borders. We assessed multiple risk pathways for three main transboundary animal diseases (foot and mouth disease, contagious bovine pleuropneumonia and peste des petits ruminants) under three different scenarios: (1) the status quo (fences as they currently are), (2) with hypothetical removal of specific fence sections, and (3) with hypothetical removal of fence sections with risk mitigation measures instituted.ResultsOur study found that hypothetical removal of these fence sections did not increase the risk of the transboundary animal diseases of interest, and that with the institution of specific risk mitigation measures (such as strategic livestock herding), the overall risk of some diseases would be lower compared to the status quo. Each pathway contained critical steps with low, very low or negligible risk which influenced the overall risk for the pathway.DiscussionBased on low estimated risks, sections of all three fences could be considered for removal, but further information was needed for the Western Border fence. Key stakeholders established consensus to move forward with consultations with local communities and to offer assistance with the implementation of risk mitigation measures (such as improved herding, kraaling) conditionally associated with potential removal of key fence sections. Opening the fences in key low-risk areas would restore connectivity for elephants and other wildlife and potentially reduce human-wildlife conflict in areas where high densities of elephants are constrained by fences. This new, more sectorally integrative approach to livestock disease control is vital to wildlife’s ability to access key resources over space and time and thus to the sustained success of KAZA.